Perception of Russia in the Finnish public consciousness - Jussi Laine (Сравнительная политика, 2016)
Abstract: Finland and the Russian Federation share signifi cant overlaps in history. With the exception of a couple of confl icts, the relationship between the two is commonly described as friendly. With a common border of more than 1.300 kilometers, Finland has always been closely tied to its eastern neighbor. Despite the physical proximity, the Cold War era closure of the border increased the mental distance between the two sides, and fostered an image of the other colored largely by attitudinal stereotypes. For a long time, a good fence indeed made good neighbors. The resultant ‘us’ versus ‘them’ mentality etched in the minds of many has proven to be far more deeply rooted and harder to erase than the political border per se. In an attempt to trace the development of the portrayed image of Russia, this article analyzes the opinion columns featured in the main Finnish newspaper Helsingin Sanomat during 1990–2010. The analysis suggests that little effort has been made to improve the popular geopolitical image of Russia. While understanding the potential of having Russia as a neighbor, many Finns continue to actively reconfi rm the elements in the neighbor, which should be let go in order move beyond stereotypes. This tendency is only reinforced by the load of the language used in the opinion writings, which seems to inhibit people from critically evaluating the opinions and views that they hold. Myths about Russia are used for transferring ideological norms and dominant historical values of Finnish culture. Therefore, myths serve to make collective views and convictions natural and evident, even if they ungrounded. Stronger is the main myth, easier it is for both the author (the message’s sender) and the reader (the message’s recipient) to fi nd a common interpretation. As a result, it creates a code which can be understood only by those who know it and possesses a respective social knowledge.